BATAS PELAKSANAAN MASA IDDAH BAGI PEREMPUAN PERSPEKTIF EMPAT IMAM MADZHAB - Zakiyah Nur Aini; Ach. Faisol; Abd Wafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
The dissolution of marriage between husband and wife makes it obligatory for Muslim women to perform iddah. However, not a few Muslim women in Indonesia do not understand the implementation due to lack of knowledge about religion. The need to re-examine the limits of the implementation of iddah in order to help Muslim women understand about iddah and to add references to fiqh activists in understanding iddah. Many fiqh scholars provide arguments related to iddah such as Hanafi priests, Maliki priests, Shafi'i priests, and Hanbali priests. This study discusses the arguments of the madhhab imam in determining the limits of the implementation of the iddah period and the legal istinbath method used in its determination. This study uses a library method that takes library sources, namely fiqh books, books, and articles that discuss iddah. The results of the study concluded that the four priests agreed to use the legal istinbath method which was sourced from the Qur'an because the explanation was clear regarding the implementation of iddah. Then the arguments of the four madhhab priests are also not much different regarding the implementation of different iddah only in the minimum and maximum limits of its implementation set by each madhhab scholar.